'Candidatus Oscillochloris kuznetsovii' a novel mesophilic filamentous anoxygenic phototrophic Chloroflexales bacterium from Arctic coastal environments. Issue 19 (5th October 2020) - Gaisin, Vasil A; Grouzdev, Denis S; Krutkina, Maria S; Ashikhmin, Aleksandr A; Sinetova, Maria A; Osipova, Natalya S; Koziaeva, Veronika V; Gorlenko, Vladimir M
ABSTRACT: Chloroflexales bacteria are mostly known as filamentous anoxygenic phototrophs that thrive as members of the microbial communities of hot spring cyanobacterial mats. Recently, we described many new Chloroflexales species from non-thermal environments and showed that mesophilic Chloroflexales are more diverse than previously expected. Most of these species were isolated from aquatic environments of mid-latitudes. Here, we present the comprehensive characterization of a new filamentous multicellular anoxygenic phototrophic Chloroflexales bacterium from an Arctic coastal environment (Kandalaksha Gulf, the White Sea). Phylogenomic analysis and 16S rRNA phylogeny indicated that this bacterium belongs to the Oscillochloridaceae family as a new species. We propose that this species be named ' Candidatus Oscillochloris kuznetsovii'. The genomes of this species possessed genes encoding sulfide:quinone reductase, the nitrogenase complex and the Calvin cycle, which indicate potential for photoautotrophic metabolism. We observed only mesophilic anaerobic anoxygenic phototrophic growth of this novel bacterium. Electron microphotography showed the presence of chlorosomes, polyhydroxyalkanoate-like granules and polyphosphate-like granules in the cells. High-performance liquid chromatography also revealed the presence of bacteriochlorophylls a, c and d as well as carotenoids. In addition, we found that this bacterium is present in benthic microbial communities of various coastal environments of the Kandalaksha Gulf. Abstract : Arctic coastal environments harbor the novel filamentous multicellular phototrophic Chloroflexi bacterium.